Assessment of spasticity after stroke using clinical measures: a systematic review. (4th December 2015) - Aloraini, Saleh M.; Gäverth, Johan; Yeung, Ellen; MacKay-Lyons, Marilyn
Abstract: Purpose : To identify and appraise the literature on clinical measures of spasticity that has been investigated in people after stroke. Methods : The literature search involved four databases (PubMed, CINAHL, Embase and The Cochrane Library) up to February 2014. The selected studies included those that aimed to measure spasticity using a clinical assessment tool among adult patients post-stroke. Two independent raters reviewed the included articles using a critical appraisal scale and a structured data extraction form. Results : A total of 40 studies examining 15 spasticity assessment tools in patients post-stroke were reviewed. None of the reviewed measurement tools demonstrated satisfactory results for all psychometric properties evaluated, and the majority lacked evidence concerning validity and absolute reliability. Conclusion : This systematic review found limited evidence to support the use of most of clinical measures of spasticity for people post-stroke. Future research examining the application and psychometric properties of these measures is warranted. Implications for Rehabilitation: There is a need for objective clinical tools for measuring spasticity that are clinically feasible and easily interpreted by clinicians. This review identified various clinical measures of spasticity that have been investigated in people after stroke. Insufficient evidence of psychometric properties precludes recommending one tool over the others. Future research should focus on investigating the psychometric properties of clinical measures of spasticity.